Klotho null mutation leads to retinal degeneration characterized by functional impairment, gliosis, and deposition of amyloid-beta and hyperphosphorylated tau proteins - Zhi-jia Chen; Chun-Yen Wu; Fang-Yan Hsiao; Jing-Chun Ma; Gabriel Lai; Han-Hsin Chang; David Pei-Cheng Lin (PLoS ONE, 2025)
Background Klotho mutation has been known to accelerate aging and degenerative pathogenesis, notably in the kidney and the brain. Nevertheless, the aftermath of Klotho function deprivation in the retina has not been detailed. This study aimed to provide an in-depth analysis of retinopathy caused by Klotho mutation. Results The homozygous Klotho mutant mice retinas were analyzed at the 6th, 8th and 10th weeks of age, along with their heterozygous, and wild-type littermates between both genders. The electroretinogram results showed retinal function impairment with Klotho null mutation, as compared with their littermates. Nevertheless, there was no difference in the retinal layer thickness, morphology, and cell death up to 10 weeks of age among the three genotypes. No evident damage was detected in the photoreceptors, interneurons, and retinal ganglion cells with Klotho mutation up to 10 weeks of age. Amyloid-beta and hyperphosphorylated tau protein deposits were detected in the Klotho mutant retina, along with glial cell activation at 10 weeks of age. Conclusions The results revealed that Klotho null mutation leads to retinal degeneration characterized by functional impairments, gliosis, and amyloid-beta and hyperphosphorylated tau protein deposition in the retina. Klotho protein function is, therefore, mandatory for the maintenance of a healthy retina. The mouse Klotho null mutation may be used as a study model for age-related retinal degeneration and Alzheimer’s disease.